Anteseden Stres terhadap Kinerja dan Kepuasan Kerja pada Wartawan di Jawa Timur - Fauzi, Akhmad (Universitas Brawijaya, Indonesia, 2008)
From analysis result which have been conducted to relation of causal, can be explained by following: (a) Job Conflict significant positive to stress work journalist. Result of examination of hypothesis with method Model Structural Equation approach of PLS yield path coefficient equal to 0,349 with p = 0.0000, is so that decided isn't it. Thereby that there are positive influence Job Conflict to stress work journalist, that is job conflict excelsior will generate ever greater job stress. (b) Work load have an effect on 10 stress work journalist, (c) Emotional exhaustion have an effect on to stress work journalist. (d) Job Stress have an effect on to journalist performance. (e) Social Support do not have the character of to weaken influence of stress work to journalist performance. Thereby that social Support not such a moderator variable weakening influence of stress work to journalist performance. Locus of Control weaken influence of stress work to journalist performance. (g) Performance have an effect on to satisfaction journalist job. (h) Appreciation have the character of can strengthen influence of performance to satisfaction of journalist job. Other meaning as finding, is concerning assessed performance as according to criterion, will give satisfaction given by assessment is superior opinion or opinion of others will not give satisfaction. Company of mass media as a institution of profit claimed to have standard assessment of performance to assess his journalist.